Algunos aspectos biológicos y del manejo en cautiverio de la Sabaleta Brycon henni Eigenmann, 1913 (Pisces: Characidae) (2006)
ABSTRACT: Brycon henni is an endemic characoid from Magdalena, San Juán, Dagua and Patía river basins (Colombia), it is catalogued as a promissory species to culture and to repopulate natural streams; this species is important for riverside populations food safety. In this review we tried to show the most relevant information about morphology, distribution, feeding, reproduction, culture, cytogenetic, ecotoxicology and population genetics of this B. henni, we demonstrated here the lack of biology and culture information. We suggested fundamental topics for culture and fisheries management technological package construction.